Velocity distributions in vegetated particle-laden flows - Kee, Shanyin. (2011)
With increasing concern about living conditions of river dwellers as well as flood irrigation methods in low-lying flood plains, it is important to find out how vegetation in the river affects the bed load of the channel so that flood mitigation measures can be implemented. Experiments were carried out to investigate velocity distributions and sediment concentration in vegetated open channel flows in the presence of sediment transport. Four different vegetation configurations are explored to characterise how sediments behave with a variation of flow depths. Roughness of the vegetation as well as uneven distribution of vegetation canopy and flexibility of vegetation were not taken into consideration in this project as rigid rods were used to model vegetation. Observations of bed form, flow velocity, turbidity and sediment concentrations are made to be compared with the variation of vegetation density and flow depth.